2020
DOI: 10.1016/j.dld.2020.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of pancreatic cysts: A prospective study on the role of intra-cystic glucose concentration

Abstract: Background: The accuracy and costs of current diagnostic methods in the differential diagnosis of pancreatic cystic lesions still has ample room for improvement. Aims:The aim of the study was to confirm the diagnostic yield of intracystic glucose in the diagnosis of pancreatic cyst subtypes. Methods:We prospectively recruited all patients who underwent Endoscopic Ultrasound with Fine Needle Aspiration of pancreatic cyst at our Institution.Results: Fifty-six patients were included in the study. We found that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…They are heterogeneous and include malignant, benign, and pre-malignant lesions, capable of evolving into invasive carcinoma over time. The differential diagnosis between intraductal papillary mucinous neoplasm, mucinous cystoadenoma and serous cystoadenoma could be made by endoscopic ultrasonography fine needle aspiration or even better with endoscopic ultrasonography through-theneedle microforceps biopsy [25], with the determination of intracystic glucose concentration, having been found to be more sensitive than the concentration of carcinoembryonic antigen [24]; however, this investigation is not carried out in our hospital.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…They are heterogeneous and include malignant, benign, and pre-malignant lesions, capable of evolving into invasive carcinoma over time. The differential diagnosis between intraductal papillary mucinous neoplasm, mucinous cystoadenoma and serous cystoadenoma could be made by endoscopic ultrasonography fine needle aspiration or even better with endoscopic ultrasonography through-theneedle microforceps biopsy [25], with the determination of intracystic glucose concentration, having been found to be more sensitive than the concentration of carcinoembryonic antigen [24]; however, this investigation is not carried out in our hospital.…”
Section: Introductionmentioning
confidence: 90%
“…In adulthood, the prevalence of incidentally found pancreatic cystic lesions is high (between 2.6% and 19.6%) [21][22][23][24]. They are heterogeneous and include malignant, benign, and pre-malignant lesions, capable of evolving into invasive carcinoma over time.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis reported 91% sensitivity and 75% specificity for glucose compared with 67% sensitivity and 80% specificity for CEA [51]. The most common cutoff of less than 50 mg/dl suggests mucinous cysts with sensitivity ranging from 89 to 92% and specificity 75% to 86% [52][53][54][55]. Pseudocysts were also noted to have low glucose levels [53].…”
Section: Glucosementioning
confidence: 99%
“…Later, several studies demonstrated that cyst fluid glucose level performs better than CEA in differentiating mucinous from nonmucinous cysts. [ 48 49 50 ] However, similar to CEA, cyst fluid glucose level was unable to diagnose malignant PCNs. Therefore, cyst fluid glucose level is a promising biomarker in diagnosing mucinous cysts.…”
Section: Cyst Fluid Tumor Biomarker and Chemical Analysismentioning
confidence: 99%